Mechanism of hypoxic precondition in regulating neural stem cell migratory capacity to brain tumor sites in vitro - Tan Suat, Cheng (Universiti Sains Malaysia, 2018)
Neural stem cells (NSCs) are pnmrtive cells Wh1ch are capable to self-renew or differentiate into various matured neuronal cells. These cells res•de in subveotricufar zone of adult mammalian bra1n, a speCialized niche thai mamtains the pluripotent stem cell characteristics. Recently, researchers reported that NSCs showed a preferential mtgration to brain tumor s1tes in vivo. opening the opportunity to use these cells as spec1al dehvery agent to dehver anti-cancer drugs to cancer si1es d1rectly to avoid unne1..-essary s1de effect on adjacent normal health cells. Here. we propose to evaluate the mtgration of NSC to glioma cells 1n vstro carrying amicancer drugs used m d;n1cal (Tamox1den and TemozolomKle) and also the natural anti-cancer drug:; ex1racted from mediCinal plant- Quercus snfedona (QI). Besides. 1n th1s study, we also proposed to optimize the migratiOn capactty vsa hypoxic precond1\Jornng method. To do thiS. NSC lsne will be cultured under physsologic<f Ol<)'9en levels (2% oxygen; lermed hypo>Oa) and the rcsuH1ng changes m NSC gene wsll be Investigated ustng real hme PCR and western blot and compared to the eels cultured under atmosphenc oxygen (21% oxygen; termed normol<ia). We found that hypoxic NSC showed maeased HIF and CXCR4 expression After that. 01 was extracted uslng soxhlet tecl'tnique wtth 100% (QI-100%) or 70% (Qt-70%) methanol solvent ICSO of Ql-1 00% and 01-70% on human NSC line (H9-hNSC) and human glsorna celll!ne (DBTRG-OSMG) were determtned using MTT assay. Both Ql-100~.- and 01-70% sh01o'ied ants-proliferative properties aga1nst OBTRG-OSMG atJCSO, but not on H9-hNSC. Free radiCals scavenging activrty (0°PH solution testlsn the 01-100% and 01-70% were found to be 97 .3±1.4% and 96 4±3 7%, respeclil>ely Concentration of tannic and gatltc acids measured ussng HPLC was 72.56 IJgtml and 43.65 IJg/mltn Ql-100% while 1n Ql-70%, the concentratsons were 72.'11 ~!ml and 43.31 jJg/ml. res[lectlVely Ta~en together, both DPPH and HPLC data indicated that both Ql eKtracts contamed tannic and gallic acids which eKhibrt 1nherent anlioKidant activity. 01-treated H9-hNSC was seeded 1n a modifted Boyden chamber to investigate Its m1grat1on capacsty towards DBTRG-OSMG. Result showed that H9-hNSC migrated towards DBTRG-05MG wsth 4-folds h1gher capacity compared to the control However, there Is no Significant different between the normoxic and hypoxic NSC migration. In additson, the migration of Ql-100% treated H9-hNSC successfully reduced the number of DBTRG-05MG cells, indicatsng the antl-GBM potenbal of these cells In condusion, we successfully denonstrated that the NSCs are able to migrate and dehver Ql extracts towards glioma sn \11110 and reduces the glioma cell number.